Strategic Planning in Conflict Management: Epistemological Potential - Boris Vasilievich Kabylinskiy (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The urgent need to manage conflict processes effectively in the commercial organizations and government institutions means high demand of the practically focused researches in the sphere of conflict management. Applied activities of managing conflict processes in modern Russia are considered as actual practically everywhere - both in public administration and business, but thus many methodological aspects demand specification and concretization. It should be noted that the heuristic resource created within conflict management doesn’t allow transition to strategic thinking in management of conflict processes. Thus strategic planning in the sphere of public administration has to consider dynamically changing format of internal political and international calls which the Russian State in the XXI century has faced. Author offers to use possibilities scientific-theoretical, and practical point of view it is absolutely necessary to investigate possibilities of new methodological basis of managing conflict processes of epistemological approach for adaptation of the conflict theory to corresponding practices in the field of strategic management.